Routing selection in mobile ad hoc network using soft computing approaches. (2018) - Ramadan, Hany; Tawfik, Ben Bella S.; Riad, Alaa El-Din M.
Routing in the mobile ad hoc network (MANET) is a challenging task and has received a great amount of attention from researchers. This paper introduces an exact reference routing model to find the shortest path (optimum route). This model is a conventional combinatorial that selects the shortest route from all possible routes. To demonstrate the use of this reference model for comparison a second model is selected which is a modified ant colony optimisation (ACO). The good selection of the heuristic parameters of the ACO model increases its matching degree with the reference one. Therefore, a training pre-processing phase is added to select the best parameters for ACO model. The two models are compared using four different criteria. These criteria are the execution time, energy consumption, the total cost, and the network lifetime. A simulation experiment is performed, and the results show that the modified ant colony algorithm is superior in execution time but consumed more energy than the reference combinatorial and its total cost is greater than or equal to the other one. The lifetime analysis shows that the reference model has better lifetime than the modified ACO model.